Mentorship of the next generation of One Health workers through experiential learning: A case of students of Makerere University - Peninah Nsamba; Innocent B. Rwego; Edwina Atusingwize; Sylvia Wanzala; Esther Buregyeya; Gabriel Tumwine; Doreen Tuhebwe; Charles Drago Kato; Angella Musewa; Joseph M. Kungu; Frank Mwiine; Peter Waiswa; et al. (CABI, 2023)
Abstract Multiple zoonotic disease outbreaks occurred in Uganda over the past two decades and have needed operationalization of the One Health (OH) Approach to respond effectively. Between 2016 and 2018, the African One Health University Network (AFROHUN) supported 61 students (25 females, 36 males) to join multisectoral and multidisciplinary government national and district task force disease response teams. The goal of joining these teams was to build and strengthen the students' disease investigation and response skills in real time using a One Health approach. Qualitative methods were used to collect student and partner responses on their field experiences. The AFROHUN project identified the experiential knowledge and skills that the students gained. Student project reports were reviewed by the joint technical teams from the university and the national/district task forces. These included training materials and disease outbreak investigation and response reports. Partnerships and collaboration between the university One Health networks and the government enabled 35 graduate and 26 undergraduate students to receive joint mentorship from the national or district task force outbreak response teams. Most participants were from degree programs in Public Health, Epidemiology, Environmental Health, Veterinary, Wildlife Sciences, and Infectious Disease Management, while few students were from social sciences. Students were mentored in seven competency-based areas of disease management: (1) biorisk management, (2) community engagement and coordination, (3) epidemiology, (4) leadership, (5) outbreak investigation and response, (6) risk communication, and (7) surveillance. In conclusion, zoonotic outbreaks provided real-life learning opportunities for students in disease outbreak investigation and response using a multidisciplinary and multisectoral approach. The identified skills can be incorporated into educational materials such as curricula and present an ideal opportunity to build partnerships for workforce development. One Health impact statement The next generation of One Health workers, those capable of working across sectors and disciplines to improve the health of animals, humans, plants, and the environment, need soft and technical skills to guarantee optimal preparedness, prevention, and response to disease outbreaks and understand the animal to human transmission dynamics of disease. In countries where emerging, re-emerging, and endemic zoonoses and hemorrhagic fevers are prevalent, it is crucial to provide these real-life or experiential training opportunities for university students, working closely in multidisciplinary teams. The "real-time" joint mentorship by the government's multidisciplinary and multisectoral outbreak response teams, during disease outbreaks, provides an opportunity to build and strengthen student skills in biorisk management, community engagement and coordination, epidemiology, leadership, outbreak investigation and response, risk communication, and surveillance.